Optimisasi Spasial Rasio Lahan dalam Pengelolaan Sumber Data Wilayah Pesisir Secara Berkelanjutan Wilayah Studi: Pesisir Selat Madura Jawa Timur (Spatial Optimization of Land Ratio in Sustainable Coastal Zone Resource Management: Study Location Madura - Dwi Wisayantono (Indonesian Journal of Geospatial, 2014)
Abstract. Agenda 21/1992 chapter 17 and Indonesia Republic Act No. 27/2007 provides a view on the management of coastal zone with the concept of sustainable development. The manifestation of the concept has been transformed into various forms of coastal research management strategies in accordance with the categories and characteristics of state elements (governance, territory and population). A dynamic development of Indonesia as a developing country, makes the issue due to land scarcity and human population arise. By using geographic-demographic approach, the correlation between every element produce different forms of relationships, which one of them is land ratio. The pattern of land ratios tend to be unbalanced (shrink) spatially and temporally. The pattern of these trends impact the entity's land (land use change, changes in land area, land productivity, environmental degradation) and the entities of population (odds work, consumption, the value of income, and poverty). Thereby, the government and local governments should have an appropriate management strategy to the dynamics relationships of human resources and coastal resources along with all the characteristic. This study examined the extent to which the condition of the land ratio can be optimized within the framework of coastal resource management strategies according to the principles of balance and sustainability. The framework is made through a process of transformation of existing land ratio to the optimum ratio of land. Research methodology begins with mapping land ratio from the global level, national level, to the study in the coastal region of the Madura Strait. Spatially, the dynamics approach of coastal resource use unit area of the ecosystem (DAS Brantas and Madura Strait) and administrative area (county and city). From the temporally land use and population dynamics data from 1971-2005 and the prediction of condition land ratio in 2014 and 2025. Optimization process is done by theory of system and theory of optimization approach. Results of spatial land ratio optimization are examined using three location theory approach, there are Alferd Weber, Melvin Greenhut- A Losch and Walter Isard. According to the optimization result, location theory analysis and geographical association, the conclusion of this research is that the spatial optimization method can describe the geographical correlation between land resources and human resources variable, so this method can be used to measure land ratio value and to measure the principle of balance, fairness and equity between regions. Optimization of spatial land ratio in coastal resource management strategies can be placed as a feedback in any planning process, utilization, monitoring and control. Keywords: the state elements, spatial optimization, the ratio of land, geo-demographic, geographical associations, coastal resources, sustainable development.